1999
DOI: 10.1097/00043426-199903000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Liver Iron Overload by T2 Quantitative Magnetic Resonance Imaging in Thalassemia

Abstract: Liver T2 values were found to be more accurate than serum ferritin in predicting liver iron overload and were not influenced by the presence of chronic hepatitis C. Therefore, MRI could serve as a noninvasive alternative to liver biopsy for the quantification of hemosiderosis in HCV+ patients with thalassemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 33 publications
5
36
0
4
Order By: Relevance
“…Signal intensity, S, was generated using the signal equation for a gradient-echo sequence. A longitudinal relaxation time of T 1 ϭ 586 ms for liver (24) was assumed, and MR parameters were chosen to correspond to two T* 2 multi-echo gradientecho sequences adopted in our institution for clinical assessment of liver iron: breath-held (TE ϭ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Gaussian-distributed complex noise, with standard deviation noise , was added to the generated signal. Different signal-to-noise ratios (SNR ϭ M 0 / noise , where M 0 is the fully relaxed magnetization) in the range 20 to 300 were evaluated.…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Signal intensity, S, was generated using the signal equation for a gradient-echo sequence. A longitudinal relaxation time of T 1 ϭ 586 ms for liver (24) was assumed, and MR parameters were chosen to correspond to two T* 2 multi-echo gradientecho sequences adopted in our institution for clinical assessment of liver iron: breath-held (TE ϭ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Gaussian-distributed complex noise, with standard deviation noise , was added to the generated signal. Different signal-to-noise ratios (SNR ϭ M 0 / noise , where M 0 is the fully relaxed magnetization) in the range 20 to 300 were evaluated.…”
Section: Simulationsmentioning
confidence: 99%
“…Thus, although the two model fits are theoretically identical under noiseless conditions, their divergence is apparent as SNR is reduced. Figure 2 compares the performance of all three curvefitting models using two different acquisition schemes (TE ϭ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Fig. 2a) and echo spacing (min TE ϭ 1 ms), all models provide accurate R* 2 estimates.…”
Section: Patient Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that the relaxation rate R2 was a useful parameter to quantify hepatic iron concentration both in human (1-7) and animal studies (8)(9)(10)(11). However, given the fact that only noninvasive methods can be used, there is no validated sequence for the determination of splenic iron concentration which is a key point for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported noninvasive quantification of hepatic iron overload using MRI methods (5). Most studies were done on humans (6)(7)(8)(9)(10)(11), only a few having been performed on rodents (12)(13)(14)(15).…”
mentioning
confidence: 99%